2019
DOI: 10.3390/jrfm12010012
|View full text |Cite
|
Sign up to set email alerts
|

Exchange Rate Volatility and Disaggregated Manufacturing Exports: Evidence from an Emerging Country

Abstract: The link between export performance and exchange rate policy has been attracting attention from policymakers, academics, and practitioners for some time, particularly for emerging countries. It has been recently claimed that implementing a policy that devalues the currency in Vietnam is an important factor for enhancing its export performance. However, it is also argued that such a policy could result in the harmful consequence of exchange rate volatility. This study analyzes the link between exchange rate dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 38 publications
(47 reference statements)
3
28
0
2
Order By: Relevance
“…The relationship between FDI and economic growth has attracted great attention from scholars around the world (Basu et al 2003;Vo et al 2019a). It is widely acknowledged that this relationship has been intensively investigated using data from a single country or a sample of many countries.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between FDI and economic growth has attracted great attention from scholars around the world (Basu et al 2003;Vo et al 2019a). It is widely acknowledged that this relationship has been intensively investigated using data from a single country or a sample of many countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The relationship between foreign direct investment (FDI) and economic growth has attracted major attention from academics and the governments of developing countries. Since economic growth is one of their main focuses, FDI attraction-related policies have been prioritized during the process of economic growth and development in these countries (Vo et al 2019a). It is widely observed that FDI mitigates the saving-investment imbalance and provides technology which is used for the production of goods and services.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies show a negative relationship (Ojeyinka and Adegboye, 2017; Falaye, 2019;Vo and Zhang, 2019;Irene et al, 2020). Similarly, Caglayan and Torres (2011) investigate the effects of the exchange rate in the Mexican manufacturing sector from 1994 to 2003 by using fixed capital investment as an intermediate channel.…”
Section: Gross Fixed Capital Formation and Manufacturingmentioning
confidence: 88%
“…The coefficient for LNOPENNESS when the currency is undervalued is greater than when the currency is overvalued (64.0550 > 49.3755). This can be explained by an increase in the volume of exports when the currency is undervalued (Vo et al 2019;Thuy and Thuy 2019). An undervalued currency raises competitiveness of exports, which allows more goods to be misinvoiced and results in high capital flight.…”
Section: The Impact Of Undervaluation On Capital Flightmentioning
confidence: 99%